Design and Performance Analysis of the Distributed Generation System Based on a Diesel Engine and Compressed Air Energy Storage. (May 2017) - Zhang, Xinjing; Chen, Haisheng; Xu, Yujie; Li, Wen; He, Fengjuan; Guo, Huan; Huang, Ye
Abstract: The distributed generation system coupled with the energy storage system could perform a 'peak shaving' function for maintaining a required power output. As a result it decreased the core engine power rating and increased integrated system's efficiency. In this study a hybrid power generation system integrated with a Compressed Air Energy Storage (DE-CAES) system was proposed. To carry out a technical analysis the design flow chart was designed and process models were developed. The simulation results were also validated by the experiment. The results revealed that integrated system's efficiency and fuel saving ratio could be increased by 6.5% and 14.4%, respectively.